2018
DOI: 10.1111/ejn.14293
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to decrease social jetlag: Reducing evening blue light advances sleep and melatonin

Abstract: The timing of sleep is under the control of the circadian clock, which uses light to entrain to the external light‐dark cycle. A combination of genetic, physiological and environmental factors produces individual differences in chronotype (entrained phase as manifest in sleep timing). A mismatch between circadian and societal (e.g., work) clocks leads to a condition called social jetlag, which is characterized by changing sleep times over work and free days and accumulation of sleep debt. Social jetlag, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 52 publications
(65 reference statements)
1
29
0
1
Order By: Relevance
“…A simple solution that may effectively block and reduce the blue portion of the light spectrum before bedtime are blue light blocking glasses and lenses . Wearing blue light blocking eyewear before and during bed time may effectively attenuate LED induced melatonin suppression and thus can potentially facilitate the adaption to new social schedules and reduce sleep disturbances and their consequences among the general population. Further, a reduction of the blue portion in artificial light during nighttime hours could protect shift workers against disorders such as cancer and cardiovascular disorders.…”
Section: Countermeasures For the Altering Effects Of The Blue Lightmentioning
confidence: 99%
“…A simple solution that may effectively block and reduce the blue portion of the light spectrum before bedtime are blue light blocking glasses and lenses . Wearing blue light blocking eyewear before and during bed time may effectively attenuate LED induced melatonin suppression and thus can potentially facilitate the adaption to new social schedules and reduce sleep disturbances and their consequences among the general population. Further, a reduction of the blue portion in artificial light during nighttime hours could protect shift workers against disorders such as cancer and cardiovascular disorders.…”
Section: Countermeasures For the Altering Effects Of The Blue Lightmentioning
confidence: 99%
“…Although excluded shifting workers, we found that alterations in sleep time during workdays and free days affected sleep timing subsequent day. 17 This misalignment between social and biological time can be described as "social jetlag." 18 The relative social jetlag was calculated as mid-sleep time on free day (MSF) minus mid-sleep time on work day (MSW), and we used the absolute social jetlag to evaluate social jetlag.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Light treatment also requires light delivery or light input manipulation systems that are easy to use and acceptable to users. Recent light treatment approaches have focused on reducing the blue light content of light to which the retina is exposed (Zerbini et al 2018), and further development of methods by which the 24-h light exposure pattern, at the work place and at home, can be manipulated is a promising avenue for the treatment of some circadian rhythm sleep-wake disorders.…”
Section: Light Treatmentmentioning
confidence: 99%